Synergistic effect of combined protopanaxatiol and ginsenoside Rh2 on antiproliferative activity in MDA-MB-231 human breast cancer cells in vitro - Guixing Ren (Taylor & Francis Group, 2018)
Breast cancer is the most common cancer in women worldwide. The antiproliferative activities of protopanaxatiol (PPT) and ginsenoside Rh2 was measured by evaluating the inhibition of MDA-MB-231 human breast cancer cell proliferation. The two-way combination of PPT and Rh2 was conducted. In the two-way combination, the EC50 values of PPT and Rh2 were 2.3- and 2.2-fold lower, respectively, than those of PPT and Rh2 alone. The combination index (CI) values were 0.55 ± 0.09, 0.65 ± 0.10, 0.79 ± 0.12, and 0.91 ± 0.14 at 50% and 95% inhibition rates. Combined PPT and Rh2 also increased the inhibition of cell invasion and migration compared with individual compounds tested in cell lines. Intracellular signalling array analysis demonstrated that phosphorylated BAD, p53, and p38 proteins were increased. The results indicate that combined PPT and Rh2 exhibits a synergistic effect in MDA-MB-231 cell proliferation.